A Versatile Cation Additive Enabled Highly Reversible Zinc Metal Anode. Issue 2 (8th December 2021) - Yao, Rui; Qian, Long; Sui, Yiming; Zhao, Guangyao; Guo, Rongsheng; Hu, Shengyu; Liu, Peng; Zhu, Haojie; Wang, Fangcheng; Zhi, Chunyi; Yang, Cheng
Abstract: Aqueous zinc metal batteries are receiving broad attention owing to their promising characteristics of low cost, high safety, and environmental benignity. However, severe side reactions over zinc metal anodes (i.e., dendrite growth and by‐product formation) dramatically limit their further development. Herein, the key problems are tackled by introducing a dual‐function electrolyte additive (ammonium cation‐based salts) to achieve long‐term and highly reversible zinc plating/stripping. Specifically, the cation can homogenize the zinc deposition via the charge shielding effect and inhibit by‐product formation by participating in the constitution of contact ion pairs. In such a way, the Zn||Zn symmetric cell stably cycles over 2145 h at a current density of 1 mA cm −2 with the overpotential of merely 25 mV. In addition, the reversibility of energy storage devices based on manganese dioxide and an activated carbon cathode is effectively enhanced. This strategy provides a promising approach for the future development of advanced aqueous metal batteries. Abstract : The introduction of a triethylmethylammonium (TMA) cation additive can homogenize zinc deposition via charge shielding effects and simultaneously inhibit by‐product formation by participating in the constitution of contact ion pairs. Based on the dual‐function of TMA cations, the Zn||Zn symmetric cell stably cycles over 2145 h with an overpotential of merely 25 mV at the current density of 1 mA cm −2 .